Causal theories of explanation and the challenge of explanatory disagreement - Jansson, Lina (University of Chicago Press, 2014)
When evaluating the success of causal theories of explanation the focus has typically been on the legitimacy of causal relations and on putative examples of explanations that we cannot capture in causal terms. Here I motivate the existence of a third kind of problem: the difficulty of accounting for explanatory disputes. Moreover, I argue that this problem remains even if the first two are settled and that it threatens to undercut one of the central motivations for causal accounts of explanation, namely, the causal account of the directionality of scientific explanation.